(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Globalization has significantly transformed global food systems by reshaping agricultural production, trade flows, dietary patterns, governance mechanisms, and environmental sustainability. While globalization has enhanced food availability, technological diffusion, and international market integration, it has also intensified inequalities, market dependency, dietary transitions, and systemic vulnerabilities. This paper critically examines the multidimensional relationship between globalization and food security across economic, social, nutritional, environmental, and political domains, with particular emphasis on India. Drawing upon recent global reports and national datasets, the study highlights the dual character of globalization as both an opportunity and a structural risk for sustainable food security. The Indian case illustrates the tension between export-led growth and domestic nutritional challenges, underscoring the importance of balanced policy frameworks that integrate global participation with local resilience.